Overview of the Role of Teachers and Peer Counselors in the Prevention of Sexual Violence in Child-Friendly Schools - Hidayah, Lissa Nur; Umaroh, Ayu Khoirotul (Universitas Ibn Khaldun Bogor, 2025)
Based on data from the Ministry of Women's Empowerment and Child Protection, in 2023, as many as 8,228 cases of violence have occurred, with the highest level of education, namely Senior High School (SMA) as many as 4,299 cases. The most victims of violence are 13-17 years old with 5,137 cases. The most common type of violence is sexual violence with 6,032 cases. Schools have an important role in preventing cases of sexual violence, one of the prevention programs that can be carried out is the establishment of a Roots change agent which aims to prevent acts of violence and bullying. The purpose of this study is to get an overview of the role of teachers and peer counselors in preventing sexual violence in child-friendly schools (Study at SMA Negeri 3 Surakarta). This research is a qualitative research with a case study approach with data collection techniques through semi-structured interviews. The research informants consisted of ten (10) main informants, three (3) triangulation informants and one (1) key informants obtained using purposive sampling techniques. The results of the study show that the role of teachers in preventing sexual violence in schools is as a companion, providing information about sexual violence and providing a good example. The role of peer counselors is to provide information about sexual violence and as an intermediary in solving peer problems. The conclusion of this study is that teachers and peer counselors play an active role in the prevention of sexual violence at SMA Negeri 3 Surakarta.